PERBANDINGAN PERTUMBUHAN JAHE MERAH (Zingiber officinale var. rubrum) MELALUI METODE PENANAMAN SECARA MANUAL DAN MENGGUNAKAN MESIN TANAM TRANSPLANTER - Kurniawan, Age; Saragih, Syaiful Amri; Jusoh, Mohd Shahmihaizan bin Mat (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
This study aims to see the effect of manual planting methods and using a transplanter machine on the growth of red ginger plants, and to see whether there is a difference in the growth and productivity of ginger plants using these two methods. This study was conducted at the Engineering Research Center, Malaysian Agricultural Research and Development Institute (MARDI), Malaysia. A total of 16,000 ginger seeds were prepared for manual planting. Then, 16,000 ginger seeds were also prepared for planting using a transplanting machine. Several parameters observed in this study, such as plant height, rhizome width, rhizome weight and number of shoots. The results showed that the average ginger growth using machine is greater than manual on all parameters. The use of a transplanting machine in ginger planting was able to produce higher plant height, rhizome width, rhizome weight and number of shoots compared to manual planting. However, only the rhizome width parameter showed a significant difference between the two treatments (p<0.05). The use of machines in the ginger planting process is not only more efficient but also able to create better conditions for rhizome growth.